Semaglutide reduces cardiovascular events regardless of metformin use: a post hoc subgroup analysis of SUSTAIN 6 and PIONEER 6 - Steve Bain (Cardiovascular Diabetology, 2022)
BackgroundCardiovascular outcome trials (CVOTs) are conducted on a background of standard of care including metformin. These analyses sought to determine whether the cardiovascular (CV) effects of semaglutide and other glucagon-like peptide-1 receptor agonists (GLP-1RAs) vary according to baseline metformin use.MethodsA post hoc analysis was conducted using pooled SUSTAIN 6 and PIONEER 6 CVOT data in subjects with and without metformin use at baseline. Additionally, a trial-level meta-analysis was conducted using data from seven CVOTs with GLP-1RAs–SUSTAIN 6, PIONEER 6, HARMONY OUTCOMES, LEADER, REWIND, EXSCEL and AMPLITUDE-O–including adults with type 2 diabetes at high CV risk, and a primary endpoint of time to first major adverse CV event (MACE).ResultsIn the post hoc analysis, the no-metformin subgroup was older, with a higher body mass index, lower estimated glomerular filtration rate and higher CV risk at baseline vs the metformin subgroup. Hazard ratios (95% confidence intervals) for the reduction in risk of MACE with semaglutide vs placebo in the metformin and no-metformin subgroups were 0.70 (0.55;0.89) and 0.86 (0.60;1.22), respectively. No significant interaction between the treatment effect on MACE and metformin subgroup was observed. Findings for other CV endpoints were similar. In the meta-analysis, treatment effect (GLP-1RA vs placebo) on CV outcomes was no different with vs without baseline metformin (overall ratio between the hazard ratios for metformin vs no-metformin 1.09 [0.96;1.22]).ConclusionThese findings indicate that the CV outcomes for semaglutide were similar regardless of baseline metformin use, which may also apply to all GLP-1RAs.